Celebrity endorsements in India - Dalal, Aadit (2017)
This research paper is based on the concept of celebrity endorsements in India and how it affects attitude towards the ad/brand/product and purchase decisions. It also explains the criteria for selection of a celebrity endorser and explains the concept from the consumer point of view.